A survey of theological seminary libraries in the greater Manila area - Simarangkir, Tunggul P.; Vallejo, Rosa M.; Picache, Ursula G. (Quezon City Institute of Library Science, University of the Philippines Diliman, 1971)
This is a survey of seven Theological Seminary Libraries in the Greater Manila Area for the school year 1969-1970. The study includes all aspects of the seminary libraries, such as objectives of the seminary and its library, administrative organization, collection, technical services, personnel, library use, library building and equipment.
Findings on the status of the libraries are presented, analyzed and compared against existing standards such as the A.L.A. Standards for College Libraries, Library Standards, 1954-1958, of the American Association of Theological Schools, Standards for Accrediting of the American Association of Theological Schools and Proposed Standards for Philippine College and University Libraries.
In conclusion, the seminary libraries may be divided into two groups, the first group consisting of five seminary libraries have a rather good status and the second group of two seminary libraries have inadequate collections. Suggestions and recommendations to improve the conditions of these libraries are presented.
Typescript.
Vita.
Special Problem (Master of Library Science)
Keywords: Theological libraries -- Philippines